Ameloblastic fibro-odontoma in a child patient: case report and literature review (Research, Society and Development, 2021)
The ameloblastic fibro-odontoma (AFO) is a mixed odontogenic tumor, with characteristics of ameloblastic fibroma, presenting enamel and dentin, which occurs more frequently in individuals aged 5 to 17 years. This paper reports na extensive case of ameloblastic fibro-odontoma in the mandible of a 3-year-old patient, discussed in comparison to cases selected from a brief literature review on the clinical characteristics, Evolution and therapeutic options for this lesion. In the last years, there was no consensus in the literature concerning its etiopathogenesis and classification, yet recently the AFO was classified as a developing odontoma. This case is in accordance with the 7 cases reported in the literature of AFO in the mandible of children aged 10 years or younger, especially concerning the lesion pattern and evolution and treatment adopted. The patient did not present relapse and exhibited local bone regeneration at the 3-year follow-up.